Keep focussing: striatal dopamine multiple functions resolved in a single mechanism tested in a simulated humanoid robot - Fiore, Vincenzo G.; Sperati, Valerio; Mannella, Francesco; Mirolli, Marco; Gurney, Kevin; Friston, Karl; Dolan, Raymond J.; Baldassarre, Gianluca (Frontiers in Psychology, 2014)
The effects of striatal dopamine (DA) on behavior have been widely investigated over the past decades, with “phasic” burst firings considered as the key expression of a reward prediction error responsible for reinforcement learning. Less well studied is “tonic” DA, where putative functions include the idea that it is a regulator of vigor, incentive salience, disposition to exert an effort and a modulator of approach strategies. We present a model combining tonic and phasic DA to show how different outflows triggered by either intrinsically or extrinsically motivating stimuli dynamically affect the basal ganglia by impacting on a selection process this system performs on its cortical input. The model, which has been tested on the simulated humanoid robot iCub interacting with a mechatronic board, shows the putative functions ascribed to DA emerging from the combination of a standard computational mechanism coupled to a differential sensitivity to the presence of DA across the striatum.